Leadership team alignment : from conflict to collaboration - Godart, Frédéric; Neatby, Jacques (Tantor Media, Inc., 2023)
Debunking much of the received wisdom regarding the sources of leadership team dysfunctionality, Leadership Team Alignment presents a targeted strategy for building and managing a top executive team to gain competitive advantage. Frederic Godart and Jacques Neatby bring a wealth of practical experience and in-depth knowledge, with over eight hundred hours of direct observation with more than fifty leadership teams across the globe and thousands of hours working with executives. With this book, they offer solutions to manage conflict and create environments that effectively address misalignments in organizations. Godart and Neatby take listeners through the dual role of leadership team members, the challenges of power games, and the risks of siloed leaders. They give clear advice on how to improve aspects of any leadership team, based on its size and structure and the nature of the organization. While organizational challenges may be inevitable, this book provides leadership teams the tools to correctly diagnose leadership team misalignment, with evidence-based remedies and strategically oriented interventions to maximize organizational performance.